Multi-Level Modelling (Dagstuhl Seminar 17492) - Almeida, João Paulo A.; Frank, Ulrich; Kühne, Thomas (Dagstuhl Reports, Schloss Dagstuhl - Leibniz-Zentrum für Informatik, 2018)
This report documents the program and the outcomes of Dagstuhl Seminar 17492 "Multi-Level Modelling". This seminar brought together researchers and industry practitioners from the fields of conceptual modeling, ontologies, and formal foundations to discuss and share the benefits of Multi-Level Modelling (MLM), to develop an agreement on MLM terminology and scope, and to drive future research directions in MLM. Some foundational presentations were given by the seminar organizers to ground the discussions and provide an initial set of open questions which would lead to the formation of the working groups. In addition, six industry representatives gave talks explaining the needs, challenges, utility, and possible issues with adoption of MLM in industry. Based on the original seminar goals, the talks, and the resulting discussions, four working groups were established to investigate: the formal and ontological "Foundations"of MLM; promising "Applications" and potential evaluation criteria for MLM methods; the "Dynamic Aspects" of MLM, such as processes and behaviour; and, the use of and impact on "Model Transformations" in the context of MLM.
Keywords: metamodeling; multi-level modeling